Evaluation of photocatalytic properties of zinc and cobalt mixed oxide recycled from spent Li-ion and Zn–MnO2 batteries in photo-Fenton-like process. (June 2023) - Betim, F.S.; Marins, A.A.L.; Coelho, E.L.D.; Lelis, M.F.F.; Freitas, M.B.J.G.
Highlights: Green and sustainable recycling of spent Li-ion and Zn–MnO2 batteries. Synthesis of ZnCo2 O4, ZnO and Li(Mn0.75 Ni0.25 )2 O4 from spent Li-ion and Zn–MnO2 batteries. ZnCo2 O4, ZnO and Li(Mn0.75 Ni0.25 )2 O4 as an efficient catalyst in the photo fenton like process. Recycling Li-ion and Zn-MnO2 batteries is important for the preservation of the environment. Abstract: In this study, ZnCo2 O4 –ZnO–Li(Mn0.75 Ni0.25 )2 O4 mixed oxide was synthesized by green recycling of spent Li-ion and Zn–MnO2 batteries. The cathode of Li-ion batteries and the anode of Zn–MnO2 batteries were leached separately with citric acid. Then, both leachates were mixed, and oxalic acid was added, yielding an oxalate precursor material. The precursor was calcined at 450 °C for 3 h to afford a mixed oxide. Oxalate precursor and oxide structure, composition, and morphology were determined by X-ray diffraction, inductively coupled plasma optical emission spectroscopy, Fourier-transform infrared spectroscopy, Raman spectroscopy, scanning electron microscopy, energy-dispersive X-ray spectroscopy, and transmission electron microscopy. The photocatalytic properties of the mixed oxide were evaluated in the decolorization of methylene blue dye in aqueous solution under UVC radiation. The system composed of UVC radiation + H2 O2 + catalyst reached a decolorization efficiency of 93% after 90 min of reaction. Graphical abstract: Image, graphical abstract